Risk and incidence of breast cancer in transgender individuals: a systematic review and meta-analysis. Issue 3 (16th May 2023) - Corso, Giovanni; Gandini, Sara; D'Ecclesiis, Oriana; Mazza, Manuelita; Magnoni, Francesca; Veronesi, Paolo; Galimberti, Viviana; La Vecchia, Carlo
Abstract : Background and aims: The risk of developing breast cancer in transgender individuals [male-to-female (MtF) or female-to-male (FtM)] is still inadequately quantified. We aimed to evaluate the impact of breast cancer in this population. Methods: We conducted a systematic literature search and review using the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines through the PUBMED and SCOPUS databases. We identified six cohort studies (for both populations) plus 35 case reports. Incidence and breast cancer risk quantification were the main outcomes considered. Results: FtM individuals had a higher risk of developing breast cancer in comparison to cisgender men [standardized incidence ratio (SIR) = 63.4; 95% confidence interval (CI), 32.2–124.9] but a lower risk than cisgender women (SIR = 0.42; 95% CI, 0.07–2.41). Similarly, MtF individuals were at higher risk of developing breast cancer in comparison to cisgender men (SIR = 22.5; 95% CI, 5.54–91.8) and at lower risk than cisgender women (SIR = 0.30; 95% CI, 0.22–0.42). Conclusion: In this systematic study and meta-analysis, we identified that FtM and MtF individuals are at substantially higher risk of developing breast cancer in comparison to cisgender men, though at lower risk than cisgender women. These individuals, in the absence of defined guidelines for breast cancer prevention, should periodically undergo breast or chest examinations.